Multi-specifity of Augustin’s pedagogy: Bulding the Christian paideia - Victoria Konstantinovna Pichugina (Религия, церковь, общество, 2018)
Aurelius Augustine’s contribution to philosophy, theory and practice of education is traditionally evaluated as his key ideas, which were once put forward and then passed a long and complicated path of evolution, resulting in the «pedagogical credo». This article attempts to deviate from this logic of research and consider the heritage of Augustine as an extensive corpus of the texts of different genres focused on the problem of the formation of Christian paideia. For Augustine, the ancient Greek engkuklios paideia was mainly educational practice that could become the basis for the formation of a new form of interaction between a Christian mentor and an adult student. The article describes the program of Christian liberal education of Augustine, which includes seven disciplines: grammar, rhetoric, dialectics, music, geometry, arithmetic and philosophy. According to Augustine, studying of this program led a student to happiness and wisdom, and also opened up broad opportunities for self-development and self-education throughout his life. The process of learning was considered by Augustine as a «journey to God» under the guidance of a mentor, thanks to whom the knowledge received through contemplation turned into knowledge given through Revelation.